Penerapan Model Pembelajaran Kooperarif Tipe Team Assisted Individualization (TAI) Terhadap Hasil Belajar Siswa Kelas XI IPS pada Mata Pelajaran Akuntansi di SMA Negeri 1 Sesenapadang - Ria Ria; Sahade Sahade; Fajriani Azis (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Application of the Team Assisted Individualization (TAI) Type Cooperative Learning Model to the Learning Outcomes of Class XI IPS Students in Accounting Subjects at SMA Negeri 1 Sesenapadang. Supervised by Mr. Sahade, S.Pd., M.Pd and Mrs. Fajriani Azis, S.Pd., S.E., M.Si. This research is included in the type of Classroom Action Research (PTK). This research aims to determine the application of the Team Assisted Individualization (TAI) Type Cooperative Learning Model to the Learning Outcomes of Class XI IPS Students in Accounting Subjects at SMA Negeri 1 Sesenapadang. (X) and learning outcomes as the dependent variable (Y). The population in this study was 30 students of class The data collection techniques used are observation and tests. The data analysis technique used is descriptive percentage analysis. The results of this research show that, based on the results of descriptive analysis, there is an increase in students' cognitive, affective and psychomotor learning outcomes after the implementation of the team assisted individualization (TAI) type cooperative learning model.